Bacteroides fragilis capsular polysaccharide A ameliorates ulcerative colitis in rat by recovering intestinal barrier integrity and restoring gut microbiota - Zhong, Yijia; Chang, Xiujuan; Zhao, Zihan; Zheng, Lijun; Kuang, Gaobo; Li, Ping; Liu, Chenxuexuan; Fan, Yuqin; Liang, Zhixuan; Zhuang, Ke; Xie, Qiuling; Liu, Yangyang (Frontiers in Pharmacology, 2024)
Bacteroides fragilis (B. fragilis) is a Gram-negative, obligate anaerobic, commensal bacterium residing in the human gut and holds therapeutic potential for ulcerative colitis (UC). Previous studies have indicated that capsular polysaccharide A (PSA) of B. fragilis is a crucial component for its effectiveness, possessing various biological activities such as anti-inflammatory, anti-tumor, and immune-modulating effects. We previously isolated and characterized the B. fragilis strain ZY-312 from the feces of a healthy breastfed infant, and extracted its PSA, named TP2. In this study, we explored the impact of TP2 on colonic inflammation and delved into its potential mechanisms. Initially, we used 2,4,6-trinitrobenzenesulfonic acid (TNBS) to induce colitis in rats and found that TP2 treatment significantly ameliorated TNBS-induced weight loss, increased clinical scores, extensive ulcers, and intestinal epithelial damage in UC rats. Further analysis revealed that TP2 effectively restored the intestinal barrier integrity in UC rats by regulating the expression of Muc-2, tight junction proteins (ZO-1, occludin, claudin-1, and claudin-2), as well as apoptosis-related proteins Bcl-2, BAX, and Cleaved-Caspase-3. Additionally, TP2 suppressed the expression of pro-inflammatory cytokines TNF-α, IL-1β, IL-6, and IL23, while promoting the secretion of anti-inflammatory cytokines IL-10 and IL-22, thereby inhibiting the occurrence of inflammation. TP2 also downregulated the phosphorylation levels of AKT and PI3K, effectively inhibiting the abnormal activation of the PI3K/AKT signaling pathway. More interestingly, 16S rRNA sequencing results showed that TP2 restored the ecological imbalance of the rat intestinal microbiota, with an increase in beneficial bacteria such as Lactobacillus and Limosilactobacillus observed in the treatment group. In conclusion, TP2 through the regulation of intestinal barrier-related cells and proteins, inhibition of apoptosis, modulation of inflammation-related cytokine levels, and control of abnormal activation of the PI3K/AKT signaling pathway, restores intestinal barrier integrity. Additionally, by reshaping the ecological imbalance of the gut microbiota, TP2 ultimately alleviates ulcerative colitis in rats.